Factors Associated With Lameness in Tie Stall Housed Dairy Cows in South Germany - Oehm, Andreas W.; Jensen, Katharina Charlotte; Tautenhahn, Annegret; Mueller, Kerstin-Elisabeth; Feist, Melanie; Merle, Roswitha (Frontiers in Veterinary Science, 2020)
Lameness remains a major concern for animal welfare and productivity in modern dairy production. Even though a trend towards loose housing systems exists and the public expects livestock to be kept under conditions where freedom of movement and the expression of natural behavior are ensured, restrictive housing systems continue to be the predominant type of housing in some regions. Factors associated with lameness were evaluated by application of multiple logistic regression modelling on data of 1006 dairy cows from 56 tie stall farms in Bavaria, South Germany. In this population, approximately every fourth cow was lame (24.44% of scored animals). The mean farm level prevalence of lameness was 23.28 %. In total, 22 factors were analyzed regarding their association with lameness. A low Body Condition Score (BCS) (OR 1.54 [95%-CI 1.05 – 2.25]) as well as increasing parity (OR 1.41 [95%-CI 1.29 – 1.54]) entailed greater odds of lameness. Moreover, higher milk yield (OR 0.98 [95%-CI 0.96 – 1.00]) and organic farming (OR 0.48 [95%-0.25 – 0.92]) appeared to be protectively associated with lameness. Cows with hock injuries (OR 2.57 [95%-CI 1.41 – 4.67]) or with swellings of the ribs (OR 2.55 [95%-CI 1.53 – 4.23]) had higher odds of lameness. A similar association was observed for the contamination of the lower legs with distinct plaques of manure (OR 1.88 [95%-CI 1.14 – 3.10]). As a central aspect of tie stall housing, the length of the stalls was associated with lameness; with stalls of medium (centimeters) (OR 2.15 [95%-CI 1.29 – 3.58]) and short length (OR 4.07 [95%-CI 2.35 – 7.05]) increasing the odds compared with long stalls (> 171 centimeters). These results can help both gaining knowledge on relevant factors associated with lameness as well as approaching the problem of dairy cow lameness in tie stall operations.